A holding access-point assignment algorithm for IEEE802.11 wireless local-area networks. (2018) - Tajima, Shigeto; Funabiki, Nobuo; Higashino, Teruo
Nowadays, various types of access-points ( APs ) and hosts such as dedicated APs, laptop personal computers (PCs), and mobile terminals have been used in IEEE802.11 wireless local-area networks ( WLANs ). As a result, the optimal assignment of holding APs with different types into the network field, depending on the host type distribution, has become another important task to design high-performance WLANs. In this paper, we first define this holding access-point assignment problem as a combinatorial optimisation problem and propose its two-phase heuristic algorithm. Then, since plural partially overlapping channels are available in IEEE802.11 WLANs, we present the channel assignment extension to the APs such that the communication time of the APs is minimised, and the model to estimate the communication time increase by interferences. The effectiveness of our proposal is verified through simulations in six instances using the WIMNET simulator.